2019
DOI: 10.1097/md.0000000000013909
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 inhibition versus mTOR blockade as second-line strategy in postmenopausal patients with hormone receptor-positive advanced breast cancer

Abstract: Background:Cyclin-dependent kinase 4/6 (CDK4/6) inhibitors (palbociclib and abemaciclib) and mammalian target of rapamycin (mTOR) inhibitors (everolimus) are effective agents for restoring endocrine sensitivity in patients with advanced breast cancer progression on prior aromatase inhibitors. We conducted a network meta-analysis to compare these treatments in terms of progression-free survival (PFS), objective response rate (ORR), and clinical benefit rate (CBR).Methods:The PubMed and Embase databases were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…One previous network meta-analysis involving six trials with 4,063 patients indirectly compared the efficacy of palbociclib, abemaciclib and everolimus for restoring endocrine sensitivity and demonstrated that the combinations of palbociclib or abemaciclib with fulvestrant showed similar efficacies to everolimus plus exemestane in terms of PFS and ORR [ 43 ]. This finding indicates that the efficacies of CDK4/6 inhibition and mTOR blockade are similar.…”
Section: Discussionmentioning
confidence: 99%
“…One previous network meta-analysis involving six trials with 4,063 patients indirectly compared the efficacy of palbociclib, abemaciclib and everolimus for restoring endocrine sensitivity and demonstrated that the combinations of palbociclib or abemaciclib with fulvestrant showed similar efficacies to everolimus plus exemestane in terms of PFS and ORR [ 43 ]. This finding indicates that the efficacies of CDK4/6 inhibition and mTOR blockade are similar.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent AEs are hyperglycemia, stomatitis, anemia, dyspnea, and fatigue and this led to dose reduction in two-thirds of patients and a therapy discontinuation in more than 12% in several studies [ 74 ]. However, a network analysis showed a similar significant improvement of PFS in studies with CDK4/6 inhibitor- based combinations compared with studies with everolimus plus exemestane; no randomized trial of both these combinations has been performed [ 75 ]. An improvement of OS was observed in randomized phase III studies with everolimus, but without statistical relevance [ 76 ].…”
Section: Alternative Therapeutic Approaches For Patients With Cdk4/6 Inhibitor Resistancementioning
confidence: 99%
“…There is some data suggested that the CDK4/6I may show some benefit of HR+/HER2+ABC. 50 Many ongoing phase II and III trials to justify the role of CDK4/6I with anti-HER2 therapy in HR+/HER2+ABC; NCT02448420, palbociclib, and trastuzumab±letrozole; NCT02947685, anti-HER-2 therapy/ET±palbociclib; NCT02657343, ribociclib in combination with trastuzumab or T-DM1.…”
Section: The Next Step In Cdk4/6imentioning
confidence: 99%